A low-volume Nordic hamstring curl programme improves change of direction ability, despite no architectural, strength or speed adaptations in elite youth soccer players - Siddle, J.; Weaver, K.; Greig, M.; Harper, D.; Brogden, C. M. (Research in Sports Medicine, 2022)
Nordic hamstring curls (NHC) are a commonly used injury intervention method in amateur team sports. Seventeen elite male academy soccer players performed an 8-week low volume NHC programme. Pre-post intervention measures of isokinetic eccentric knee flexor (KF) strength, linear speed, COD performance, hamstring muscle thickness, pennation angle and fascicle length were recorded. No significant main effects were observed for measures of isokinetic KF strength (P = 0.19), linear sprint speed (P = 0.47) or hamstring muscle architecture (P = 0.30). However, significance was noted for improved COD performance (P < 0.01; mean difference, -0.06, p = 0.001, 95% CI = 0.03 to 0.09; d = 0.80), exceeding the minimal detectable difference (MDD = 0.05 s). A low-volume NHC intervention may contribute to significant improvements in COD ability, independent of no significant changes in eccentric KF strength, linear sprint speed or muscle architectural properties in elite youth soccer players.